Condylar changes after orthognathic surgery for class III dentofacial deformity: a systematic review. Issue 2 (February 2019) - Vandeput, A.-S.; Verhelst, P.-J.; Jacobs, R.; Shaheen, E.; Swennen, G.; Politis, C.
Abstract: After orthognathic surgery for class II dentofacial deformity, remodelling of the mandibular condyle will take place. In a number of cases, this may evolve towards a phenomenon of condylar resorption. Yet, studies on the occurrence of this complication after the correction of a class III deformity are scarce. A systematic review of the literature was performed with the aim of identifying reports on condylar resorption or remodelling after orthognathic surgery for class III dentofacial deformity. A search of the international databases yielded 12 eligible studies. Eight studies reported some degree of postoperative condylar remodelling, while symptoms of condylar resorption were only described in a limited group of patients. Thus, the literature may show evidence of condylar remodelling after orthognathic treatment of class III patients, and anecdotal reports of condylar resorption exist. The small sample sizes, heterogeneity in methods and outcomes, and use of two-dimensional radiographs indicate the need for updated long-term research. In the future, the use of cone beam computed tomography data for volumetric and morphological condylar analysis in combination with three-dimensional cephalometry may provide the opportunity to further elucidate this phenomenon and better characterize its aetiology.